A novel sequential synthesis algorithm for the integrated optimization of Rankine cycles and heat exchanger networks. (25th June 2021) - Elsido, Cristina; Cremonesi, Andrea; Martelli, Emanuele
Highlights: Structure of both Rankine cycle and HEN are optimized in an integrated way. A novel sequential algorithm for the MINLP solution is devised. The method aims to identify the best trade-off between cycle efficiency and costs. Very good performance compared to three literature approaches indicate. Six real-world case studies show the effectiveness of the proposed algorithm. Abstract: The research theme of this work is the optimization of the heat integration and heat recovery in energy systems and chemical processes, specifically, the optimal synthesis and design of Rankine cycles (e.g., heat recovery cycles, heat pump cycles, etc.) integrated with the heat exchanger network. The challenging synthesis problem is formulated as a Mixed Integer NonLinear Program and tackled with a novel sequential algorithm based on the idea of optimizing the independent mass flow rates of the Rankine cycle superstructure with a derivative-free algorithm. At the lower level, for fixed Rankine cycle and utility mass flow rates, the synthesis of the heat exchanger network is performed with an efficient sequential algorithm. The proposed algorithm is compared against three state-of the-art approaches on six real-world case studies including Organic Rankine cycles, heat pumps/CHP cycles and heat recovery steam cycles with multiple pressure levels. Results indicate that the proposed algorithm finds optimal or near-optimal design solutions for all case studies proving its applicability as an effective design tool.